Micropuncture studies of proximal tubule albumin concentrations in normal and nephrotic rats - Oken, Donald E. (1971)
The concentration of serum albumin in proximal tubule fluid of normal rats and animals with aminonucleoside nephrosis was studied using renal micropuncture techniques. Albumin was quantitated by an ultramicrodisc electrophoresis method capable of measuring 3 χ 10(-11) g of albumin, in 10 nl volumes. With this sensitivity, only small samples of tubule fluid were required for analysis. Collection times could be kept short, therefore decreasing the opportunity for sample contamination with extraneous serum albumin. The measured mean concentration of albumin in proximal tubule fluid (1 mg/100 ml in females and 0.7 mg/100 ml in males) was somewhat lower than values reported by others, but even these values are apt to have been artifactually high as a result of animal preparation and trace contamination of samples during micropuncture. Rats injected with aminonucleoside of puromycin 4 days earlier, showed a significant increase in tubule-fluid albumin concentration coincident with a fall in serum albumin concentration and a 43-fold increase in urine albumin concentration. Tubular absorption of albumin was small relative to that of water. Although albumin filtration was significantly increased over that in normal animals, the glomerular basement membrane still served as a highly efficient barrier to albumin transfer.